1821–2021: Contributions of physicians and researchers of Greek descent in the advancement of clinical and experimental cardiology and cardiac surgery - Gerontas, Apostolos; Avgerinos, Dimitrios; Charitakis, Konstantinos; Maragou, Helena; Drosatos, Konstantinos (Frontiers in Cardiovascular Medicine, 2023)
While the role of Greeks in the development of early western medicine is well-known and appreciated, the contributions of modern Greek medical practitioners are less known and often overlooked. On the occasion of the 200-year anniversary of the Greek War of Independence, this review article sheds light onto the achievements of modern scientists of Greek descent in the development of cardiology, cardiac surgery, and cardiovascular research, through a short history of the development of these fields and of the related institutions in Greece. In the last decades, the Greek Cardiology and Cardiac Surgery communities have been active inside and outside Greece and have a remarkable presence internationally, particularly in the United States. This article highlights the ways in which Greek Cardiology and Cardiovascular Research has been enriched by absorbing knowledge produced in international medical centers, academic institutes and pharmaceutical industries in which generations of Greek doctors and researchers trained prior to their return to the homeland; it also highlights the achievements of medical practitioners and researchers of Greek descent who excelled abroad, producing ground-breaking work that has left a permanent imprint on global medicine.